Evaluation of toxic compounds and quality parameters on the aged Brazilian sugarcane spirit (Research, Society and Development, 2020)
The typical Brazilian sugarcane spirit, called “cachaça”, is a drink known and marketed throughout the world. Its worldwide popularity was due to the drink called caipirinha, where cachaça is used as one of its main ingredients. Thus, there is a growing concern with its quality. Among the limiting factors for the quality of cachaça from the point of view of food security and suitability for trade and export, the presence of toxic compounds is one of the most important.  Some toxic compounds may be present in the cachaça through contamination or formation during the production stages. Aiming to investigate the presence of some of these compounds in cachaças from Bahia, twenty-seven samples of aged cachaças were collected and analyzed regarding their identity and quality standards. For this purpose, analyzes of quality parameters in relation to alcohol content, acidity, copper, furfural, methanol, ethyl carbamate, higher alcohols, butan-1-ol, and butan-2-ol. Regarding the quality standards, while 74.1% of the samples were not in conformity with the limit established by the law concerning the contents of toxic compounds such as copper, furfural, or ethyl carbamate. Knowledge on the quality of Brazilian cachaça is of great importance for its recognition, since it is marketed throughout the country with growing insertion into the international market.